PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL PERMAINAN TRADISIONAL GALASIN - Nurmaidah; Muttaqin, Muhammad Fauzan; Miftachudin (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
This research aims to identify the character values contained in the traditional game of galasin, develop a character education model based on the traditional game of galasin that can be implemented in elementary schools, and measure the effectiveness of the model in improving students' character values. This research was conducted on 4th grade students at SD Islam Ash-Syakirin. Using a qualitative approach with a descriptive method, this research involves students, teachers, and principals as the main subjects. Data were collected through participatory observation (four observations), in-depth interviews, and documentation studies, and validated using method triangulation techniques. The results of the study showed that the Galasin game taught students important values such as cooperation, tolerance, sportsmanship, and respect for diversity. Through these games, students learn to appreciate differences, interact with friends from different backgrounds, and build an inclusive attitude in daily life. In addition, the role of teachers in directing and reflecting on students' experiences during play has a great influence on the understanding of global diversity values. The traditional Galasin game not only serves as entertainment, but also as an effective means of character education in strengthening the sense of unity and togetherness in the school environment. Therefore, the integration of traditional games in learning in elementary schools needs to be developed in order to instill character values that are relevant to community life.